Princess Matilda (Parragon, 2010)
A little girl named Matilda spends her time playing the roles of a beautiful princess, an angry witch, a clown, and a butterfly.

Train! (Tiger Tales, 2015)
A train-loving baby elephant is excited to go on a real train, but when the other baby animals want to play with different vehicles, he becomes upset, until he tries some of the other toys for himself.

How do dinosaurs play with their friends? (Blue Sky Press, 2006)
Rhyming text and illustrations present some of the ways dinosaurs can play with their friends, from hogging the swings to sharing toys.

Teddy bear (Child's Play, 2004)
Description Not Provided

Baa baa, black sheep! (Sign and sing-along, ,, 2004)
Presents a familiar nursery rhyme accompanied by illustrations showing how to form the American Sign Language signs for each word.

There's a monster in your book (Random House, 2017)
Encourages the reader to shake, tilt, and wiggle the book to remove the little monster inside, but once it is out, another problem arises.